Person and Humanity of the Son of God: Theological Contributions about the Person of Jesus - Zarazaga, Gonzalo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This paper is an investigation into the mystery of the incarnation motivated by the issue of the human nature and the person of Jesus. The author offers a status quaestionis by analyzing the views advanced by recognized theologians such as A. Grillmeier, K. Rahner, J.-H. Nicolas, W. Kasper, B. Sesboüé, P. Coda The analysis shows that Chalcedon left open a formula for the search of a more integral, dynamic, and deeper understanding of the mysterious human-divine reality of Jesus. The article makes some contributions on this search.
Keywords: person; relation; phenomenology; becoming; kenosis; event